Community Psychology in Latin America and the Caribbean: a systematic literature review - Lopes de Souza, Leticia; Vitor dos Reis, Mateus; Corrêa Netto, Weverton; Mota Ronzani, Telmo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Latin American Community Psychology is understood from its direct relation with the social, political and economic formation of the continent. In this sense, the present study aimed at conducting a systematic review of the academic production on Community Psychology in Latin America and the Caribbean. The search for the descriptors "Community Psychology"; "Community Social Psychology"; "Psicologia Comunitária" and "Psicologia Social Comunitária" was made in the databases BVS, PubMed, PsycNET, Lilacs, Pepsic, IndexPsicPeriod and Scielo, in English, Spanish and Portuguese, from 2012 to 2021. The final sample brings together 72 studies which were classified according to the categories: descriptive data; type of publication; populations and communities; territories; diversity of perspectives of action; and research methods and techniques. The results show that there is an approximation of Community Psychology with communities and populations marked by situations of inequality and oppression, and also a theoretical and methodological plurality in the articles analyzed. It was also observed that there is not much approximation with rural territories in comparison to urban territories, and the absence of articles that make a specific gender approach. Finally, the importance of a greater number of studies based on participatory research perspectives is highlighted.